Therapies for cardiac light chain amyloidosis: An update. (15th November 2018) - Aimo, Alberto; Buda, Gabriele; Fontana, Marianna; Barison, Andrea; Vergaro, Giuseppe; Emdin, Michele; Merlini, Giampaolo
Abstract: Light-chain (AL) amyloidosis is the most common type of systemic amyloidosis, affecting around 10 people per million per year. This serious disorder is characterized by the presence of a clone of bone marrow plasma cells that produces monoclonal light chains (LCs) of the κ or predominantly λ type. These amyloidogenic LCs undergo extracellular misfolding and aggregation into proteotoxic soluble oligomers and amyloid fibrils that deposit within tissues. The lethal consequences of AL amyloidosis are due to the toxic products (the LCs) and not to the malignant behaviour of the plasma cell clone. Almost 80% of patients with AL amyloidosis have some degree of cardiac involvement, manifesting as heart failure (HF), and carrying a particularly poor prognosis. The past decade has seen major advances in the treatment of AL amyloidosis, and a rapidly fatal disease has become a treatable and possibly curable condition. The number of therapeutic options is rapidly expanding, offering hope to address currently unmet needs (most notably, the treatment of frail patients). The treatment of AL amyloidosis consists in a combination of agents targeting multiple steps of the amyloid cascade, associated with effective HF management, and there is ground for hope for dramatically improving the outcome in the near future. In the present review we will summarize our current knowledge on therapy for cardiac AL amyloidosis, targeting clinical cardiologists involved in the care of this serious disorder. Highlights: The heart is often involved in light-chain (AL) amyloidosis. Cardiac AL amyloidosis is associated with poor prognosis. The treatment consists in a combination of agents targeting multiple steps of the amyloid cascade. These therapies must be accompanied by effective HF management.